PERANCANGAN RESORT DI PANTAI SERUYAN DENGAN TEMA THE ART OF DOING NOTHING - Esterliani; Widati, Titiani; Amiany (JURNAL PERSPEKTIF ARSITEKTUR, 2023)
Indonesia is known as a maritime and archipelagic country that has extensive offshore areas, this can be utilized as one of the developments in the tourism sector. One of the unspoiled beaches is the beach in Seruyan district, Central Kalimantan. Utilization of Seruyan Beach land by paying attention to its potential which is very quiet and far from the crowds, so it is very suitable to be used as a resort in the form of a resort to unwind from the boredom of work in the city using the theme The Art of Doing Nothing. The Art of Doing Nothing is a relaxation method that makes the simplicity of nature and the surrounding environment the most valuable things in life. To solve this problem, Organic Architecture is used as a solution to the problem by using its characteristics, namely simplicity and serenity. This can be realized by processing spatial planning, area patterns and facilities that provide appropriate activities so that they are able to answer needs with the theme The Art of Doing Nothing used.